Myeloid Clonal Infiltrate Identified With Next-Generation Sequencing in Skin Lesions Associated With Myelodysplastic Syndromes and Chronic Myelomonocytic Leukemia: A Case Series - Martin de Frémont, Grégoire; Hirsch, Pierre; Gimenez de Mestral, Santiago; Moguelet, Philippe; Ditchi, Yoan; Emile, Jean-François; Senet, Patricia; Georgin-Lavialle, Sophie; Hanslik, Thomas; Maurier, François; Adedjouma, Amir; Abisror, Noémie; et al. (Frontiers in Immunology, 2021)
Background Myelodysplastic syndromes (MDS) and chronic myelomonocytic leukemia (CMML) are associated with cutaneous manifestations. Next-generation sequencing (NGS) is a tool capable of identifying clonal myeloid cells in the skin infiltrate and thus better characterize the link between hematological diseases and skin lesions. Objective To assess whether skin lesions of MDS/CMML are clonally related to blood or bone marrow cells using NGS. Methods Comparisons of blood or bone marrow and skin samples NGS findings from patients presenting with MDS/CMML and skin lesions in three French hospitals. Results Among the 14 patients recruited, 12 patients (86%) had mutations in the skin lesions biopsied, 12 patients (86%) had a globally similar mutational profile between blood/bone marrow and skin, and 10 patients (71%) had mutations with a high variant allele frequency (>10%) found in the myeloid skin infiltrate. Mutations in TET2 and DNMT3A, both in four patients, were the most frequent. Two patients harbored a UBA1 mutation on hematopoietic samples. Limitations Limited number of patients and retrospective collection of the data. Blood and skin sampling were not performed at the exact same time point for two patients. Conclusion Skin lesions in the setting of MDS/CMML are characterized by a clonal myeloid infiltrate in most cases.